Integration of Odoo Learning Management System with Zoom Video Conferencing for K-12 Students - et. al., Benny Yustim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Many educational institutions use the Learning Management System as an e-learning application. However, the e-learning method is less effective to use because students cannot interact directly with the teacher, so it takes longer to get feedback. The purpose of this research is to make it easier for students and teacher to interact directly (synchronous learning) within the scheduled time according to the e-learning material. The system development method used in this study uses the waterfall methodology with the stages of communication, planning, modelling, construction, and deployment. The framework used is Odoo and Zoom application as video conferencing media. The expected result from developing this system is that students get the optimal benefits of e-learning by making face-to-face online learning schedules with instructors in an integrated Learning Management System (LMS).